2004
DOI: 10.1530/eje.0.1500119
|View full text |Cite
|
Sign up to set email alerts
|

Precocious puberty secondary to massive ovarian oedema in a 6-month-old girl

Abstract: A 6-month-old girl was referred with breast and pubic hair development. Investigations excluded an adrenal or central cause for her precocity. Ovarian ultrasound scans showed bilaterally enlarged ovaries with both solid and cystic changes. A follow-up examination suggested progression of the precocity and in view of the young age of the child, and concerns regarding underlying malignancy, she underwent laparotomy. Histology showed no evidence of neoplasia but there was stromal oedema consistent with a diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…[2] We had 2 cases of pseudotumoural lesions in the series: haemorrhagic cyst and massive oedema of the ovary which is a rare pseudotumoural lesion, occurring primarily in adolescents and young women and often confused with malignant tumours. [10] Malignant tumours of the ovary are infrequent in children and comprise about 3% of all childhood cancers. The risk of malignancy increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…[2] We had 2 cases of pseudotumoural lesions in the series: haemorrhagic cyst and massive oedema of the ovary which is a rare pseudotumoural lesion, occurring primarily in adolescents and young women and often confused with malignant tumours. [10] Malignant tumours of the ovary are infrequent in children and comprise about 3% of all childhood cancers. The risk of malignancy increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…3 4 The affected age group is between 6 and 33 years with a median age of 20 years. There are two types of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have demonstrated that multiple ovarian follicles situated around the periphery of the cortex of the enlarged ovary are the most important indicators of MOE. 3,4 Levels of tumor markers such as CA 125 have not been found helpful in definitely excluding the diagnosis of neoplasm, as both the sensitivity and specificity are not 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Des nausées et/ou vomissements peuvent accompagner la symptomatologie. Des cas de puberté précoce et/ou des signes de virilisation ont été décrits [2,7,8]. Chez des femmes enceintes de 13 semaines après stimulation par le citrate de clomifène, deux cas d'OMO ont été rapportés [9,10].…”
Section: Figureunclassified